La democracia como discurso: sentidos en tránsito. Análisis de la producción del significado en una localidad barrial de Asunción – Paraguay - Rossana Gómez (Nuevo mundo - Mundos Nuevos, 2014)
More than ever, in recent times, the democracy discourse in the region was governed by a two-sided social dichotomy: dictatorship/democracy. The following article aims to respond to the question: What is democracy to social beings? Thus it focuses on the inclusive definition of democracy and it analyzes socio-historic processes that parted from the aforementioned social constructs. It identifies how its conceptualization is transmitted through its construction. It utilizes the findings of an investigation that was organized in one of Paraguay’s neighborhoods, between the years of 2010 and 2012, in the context of the first governmental drift, which happened after the fall of Alfredo Stroessner’s dictatorship (1954-1989). Social transformation and displacement are become afloat due to what happened in the past, during the dictatorship, and in the present, in a democracy.The outcome that derives from this analysis comes from a communication perspective, which has a clear understanding of this social discourse and sees it as a place where meaning can be negotiated, re-created, and re-confirmed. Throughout their lives, individuals adopt social stratification through: collective identity, a variety of social-economic conceptualizations, as well as symbols, historic and cultural constructs, which then become evidence of this process.